ENHANCING STUDENTS’ ENGAGEMENT AND LEARNING OUTCOMES IN ISLAMIC EDUCATION BY LEVERAGING THE EFFECTIVENESS OF WORDWALL - Rahmah Rahmah; Muhammad Nurhadi; M. Anang Sholikhudin (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2024)
This study explored the effectiveness of Wordwall, a digital learning tool, in improving student learning outcomes in Islamic education at Junior High School N 1 Purwosari. Using a quasi-experimental design with both experimental and control groups, the research evaluates the impact of Wordwall on student performance through pre-test and post-test assessments. Statistical analyses, including descriptive statistics, normality tests, and Islamic educationred sample T-tests. Specifically, the experimental group showed a significant increase in average scored from 70.33 (pre-test) to 84.25 (post-test), while the control group's scores increased from 65.25 to 73.58. These findings underscore Wordwall's efficacy in creating interactive and engaging learning environments, thereby enhancing student comprehension and achievement in Islamic education. The study emphasized the integration of educational technologies like Wordwall to optimize learning experiences and highlights implications for educational practice and teacher training. It advocated for educators to receive training on effectively incorporating such digital tools into their teaching methodologies, ensuring they leverage the full potential of these resources. Furthermore, the research stressed that the effectiveness of educational technologies was influenced by factors such as learning design, content quality, and teaching approaches. By adopting a more interactive pedagogical style, educators can significantly enhance student outcomes. This research contributed valuable insights into the role of digital tools in contemporary education and encourages further investigation into their integration across various subjects, ultimately fostering student engagement and success in the learning process.